HEAVY RAINFALL AND TEMPERATURE PROYECTIONS IN A CLIMATE CHANGE SCENARIO OVER QUITO, ECUADOR - Serrano Vincenti, Sheila (2017)
This research analyzes daily extreme events of minimum, maximum temperatures and rain in the Metropolitan District of Quito using data of more than 30 years from the meteorological network of INAMHI (Instituto Nacional de Meteorología e Hidrología de Ecuador) using the R- ClimDex computer program. A scenario for the year 2032 combining statistical results of extreme events and physical forcing from PRECIS scenarios A2 and B2 is also presented; using the extreme value theory from extReme computer program. The results showed an increase in extreme minimum and maximum monthly temperature values in both, magnitude and frequency; and an increase in the intensity of heavy rainfall. Projections to 2022 maintain this behavior, with results that should be taken into account by policy makers and scientists due to the danger they mean for Quito’s ecosystem. // Esta investigación analiza eventos extremos a nivel diario de temperaturas mínimas, máximas y lluvias en el Distrito Metropolitano de Quito utilizando datos con más de 30 años de la red meteorológica del INAMHI (Instituto Nacional de Meteorología e Hidrología de Ecuador), y utilizando el programa R-ClimDex. Se presentan escenarios el año 2032 combinando resultados estadísticos de eventos extremos con el forzamiento físico de los escenarios A2 y B2 del modelo de cambio climático PRECIS A2 y B2, y utilizando la teoría de valores extremos del programa extReme. Los resultadosmostraron un incremento en los valoresmensualesmínimos ymáximos de temperatura tanto en magnitud y frecuencia; además de un aumento en la intensidad de lluvias extremas. Las proyecciones para 2032 mantienen este comportamiento, con resultados que deben ser tomados en cuenta por los tomadores de decisión y científicos debido al peligro que significan para el ecosistema de Quito.